Microstructural, Thermal And Mechanical Properties On The Tinbi Smuth Eutectic Solder Alloy Upon Additions Of Zirconia And Molybdenum Nanoparticles - Amares, Singh Gill (2021)
This research investigates the effects on the microstructural, thermal and mechanical properties of the low temperature lead free tin (Sn)-bismuth (Bi) solder alloy upon mechanically mixing 1 %, 2 % and 3 % molybdenum (Mo) and zirconia (ZrO2) nanoparticles separately. The solder alloy is chosen to replace the hazardous lead solder and to accommodate low temperature soldering. Nanoparticles of molybdenum (Mo) and zirconia (ZrO2) with high melting point and low density will not react with the elements in the solder alloy and exerts its influence as discrete particles. The melting temperatures with the lowest temperature were recorded for the 2 % Mo additions (139.73 °C) and the 2 % ZrO2 additions (140.89 °C). Low melting point solders serves as platform for low temperature soldering to preserve other components from high temperature thermal shock. The microstructures of the solder alloy reinforced with molybdenum (Mo) and zirconia (ZrO2) nanoparticles solder alloys consist of the typical lamellar structure of bismuth (Bi) and tin (β-Sn) with presences of nanoparticles as well. Compared with the bare solder alloy, the bismuth (Bi) area in all the percentages of nanoparticles addition were smaller except for the 2 % Mo additions because of improper segregation of the nanoparticles. The reinforced nanoparticles appeared as discrete particles on the microstructure and acted as heterogenous site for nucleation process and at the same time restricted the grain growth of the bismuth (Bi) area. The intermetallic (IMC) layer thickness for the 3 % ZrO2 added SB/Cu joint measures the thinnest (0.4804 µm) as the ZrO2 existed as discrete particles at the solder joint to prevent vast diffusion process. Whereas, in all molybdenum added solder joint, reaction between molybdenum and tin produced Mo2Sn IMC leaving no molybdenum as discrete particles. Thin IMC layer, discrete nanoparticles and other strengthening IMC’s will boost the solder joint’s strength. Hardness measurement based on microhardness values were calculated. The microhardness values of 1 % ZrO2 and 3 % Mo nanoparticles additions increases 12 % and 1.4 % each compared to the SB solder. The 3 % Mo and 3 % ZrO2 added solder joints produced the highest shear stress of 137.72 MPa and 174.26 MPa respectively, compatible with the thin IMC layer. Improvement to the contact angle, spreading area and ratio upon additions of both nanoparticles for all percentages of addition were observed with the smaller sized ZrO2 additions emerging with better results. The reinforcement of ZrO2 nanoparticles, specifically with the 3 % additions appeared to produce better improvement to the properties.